REVIEW OF THE BOOK: “PSYCHO-SOCIAL ASPECTS OF THE FEAR OF CRIME. ADAPTATION OF A QUESTIONNAIRE” WRITTEN BY EMELINA ZAIMOVA-TSANEVA, PH.D - Chavdarova, Velislava Atanasova (Psychological thought, 2025)
The review presents the monograph by Chief Assistant Professor Dr. Emelina Zaimova, “Psycho-Social Aspects of the Fear of Crime. Adaptation of a Questionnaire,” which stands out for its relevance in light of the dynamic and often extreme situations in the social environment. The topic highlights the multifaceted nature of the fear of crime through the following key aspects: how this phenomenon is defined and measured within the context of psychology and the social sciences; how certain individual and social factors influence the perception of crime; what the psychological and social consequences of fear are, including its impact on quality of life, mental health, and social cohesion; and what approaches exist for the prevention and management of fear. The author develops a reliable and valid methodology for studying the fear of crime, which can be applied both for scientific purposes and in practice, such as in forensic psychological assessments, the design of crime prevention strategies, and the improvement of societal well-being.